Polycarbonate composite products

By using a combined structure of opaque foamed polycarbonate layer and non-foamed polycarbonate film layer in the antenna shell, the problems of signal penetration performance, dimensional stability and weight in 5G technology are solved, and a wide frequency range is achieved High-efficiency signal transmission and lightweight design.

CN115397668BActive Publication Date: 2025-01-07COVESTRO DEUTSCHLAND AG
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180028022.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-05-11
Filing Date
2021-04-09
Publication Date
2025-01-07
Estimated Expiration
2041-04-09

AI Technical Summary

Technical Problem

In 5G technology, the antenna shell has shortcomings in signal penetration performance, dimensional stability and weight. The existing technology is difficult to effectively use in a wide frequency range, especially when high-frequency electromagnetic wave transmission is transmitted, and the weight of the active antenna is large. and complexity increases deployment difficulty.

Method used

Using a combined structure of an opaque foamed polycarbonate layer and a non-foamed polycarbonate film layer, the foamed layer is formed by injecting a molten composition containing a polycarbonate resin, an impact modifier and a flame retardant into the injection mold. , combined with physical or chemical foaming processes, form a polycarbonate composite product with improved signal penetration performance and dimensional stability.

Benefits of technology

It realizes improved signal penetration performance and dimensional stability in the 5G frequency band, while reducing the weight of the antenna shell and reducing signal loss. It is suitable for large-scale macro base station antennas and other electromagnetic wave equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115397668B_ABST
    Figure CN115397668B_ABST
Patent Text Reader

Abstract

The present application relates to a polycarbonate composite product, a preparation method thereof and a use thereof. The polycarbonate composite product comprises a foamed polycarbonate layer and a non-foamed polycarbonate film layer on the foamed polycarbonate layer. The polycarbonate composite product according to the present invention has reduced weight and improved signal penetration performance, and can be used as an antenna housing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of polymer composite materials. Specifically, the present invention relates to a polycarbonate composite product (which is particularly suitable for antenna housing), a preparation method thereof and a use thereof. Background Art

[0002] 5G technology is the upcoming fifth generation of wireless mobile communications technology. 5G wireless networks will support a 1,000-fold capacity increase, the connection of at least 100 billion devices, and a 10 Gb / s personal user experience, enabling extremely low latency and response times. 5G is the backbone of artificial intelligence (AI), the Internet of Things (IOT), automation, connected cars, telemedicine, smart cities, etc. The deployment of these networks will occur between 2020 and 2030.

[0003] Unlike 4G technology, 5G technology will use active antenna units [AAUs] instead of passive antenna units. The design of active antennas significantly increases the weight of the final antenna component. Considering the load weight of the pole, the stability of the antenna under strong winds, and the high installation and maintenance costs, reducing the weight of active antennas becomes particularly important, especially for macro base station antennas where the component size is quite large. In addition, dimensional stability is also critical due to the large size of the antenna housing.

[0004] 5G can cover a wide range of waves, including intermediate frequency bands below 6GHz and millimeter waves above 24GHz. Due to the high attenuation of higher frequency electromagnetic waves when encountering obstacles during their transmission, high signal transmission will be one of the key requirements for antenna protection materials used in 5G technology.

[0005] Better signal transmission performance means that the material has a low dielectric constant Dk and loss factor Df, and is stable over a wide range of frequencies and environmental conditions. If the antenna housing has a double-layer or multi-layer structure, S11 (return loss) and S21 (gain) are commonly used indicators to characterize the antenna transmission performance, and their units are dB.

[0006] There are some patent documents related to antenna housings. For example, US4896164 describes a conventional tuned layered antenna housing structure (Figure 2), in which the inner and outer layers of polyester resin / E-grade glass (glass fiber) laminate are placed on the front and rear sides of rigid polyimide foam, respectively, and have a specific thickness selected relative to conventional reflection elimination. Although the tuned layered antenna housing structure has significantly improved broadband characteristics in terms of insertion loss and return loss, the insertion loss is the smallest at 36 GHz within the range of 6-42 GHz, but the tuned structure cannot be effectively used outside two narrow bandwidths (8-12 GHz) and (27-31 GHz).

[0007] US2018 / 0241119 describes a multi-walled radar radome that not only provides high penetration of microwave signals, but also protects the radome from the threat of flying objects. However, due to the complexity of the composite system and the multi-layer / multi-wall, the composite system of the entire antenna housing is more complicated. Similarly, outside of the two 4 kHz narrow bandwidths (8-12 kHz and 26-30 kHz), the tuning structure cannot be effectively used.

[0008] Therefore, in 5G-related applications, there is still a need for an antenna housing with improved signal penetration performance, dimensional stability, and light weight. Summary of the invention

[0009] It is therefore an object of the present invention to provide an antenna housing having improved signal penetration performance, dimensional stability and light weight.

[0010] Another object of the present invention is to provide a method for preparing an antenna housing.

[0011] According to a first aspect of the present invention, there is provided a polycarbonate composite article comprising:

[0012] an opaque expanded polycarbonate layer; and

[0013] a non-foamed polycarbonate film layer on the foamed polycarbonate layer; wherein

[0014] The foamed polycarbonate layer comprises a polycarbonate resin, an impact modifier and optionally a flame retardant,

[0015] The non-foamed polycarbonate film layer comprises a polycarbonate resin and an optional UV stabilizer and has a thickness of 0.2-1.00 mm;

[0016] The ratio of the thickness of the non-foamed polycarbonate film layer to the thickness of the foamed polycarbonate layer is in the range of 1:3-1:20;

[0017] The polycarbonate composite article does not contain inorganic reinforcement materials.

[0018] According to a second aspect of the present invention, there is provided a method for preparing a polycarbonate composite article according to the present invention, comprising the following steps:

[0019] placing the non-foamed polycarbonate film on the inner surface of an injection mold and closing the mold to form a cavity; and

[0020] The foamed polycarbonate layer is formed by injecting and foaming a molten polycarbonate composition comprising a polycarbonate resin, an impact modifier, and optionally a flame retardant in the cavity.

[0021] According to a third aspect of the present invention, there is provided use of the polycarbonate composite article according to the present invention as an antenna housing.

[0022] The polycarbonate composite article according to the present invention can achieve improved signal penetration performance, dimensional stability, and weight reduction by combining a foamed polycarbonate layer and a non-foamed polycarbonate film layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present invention will be described in more detail below with reference to the accompanying drawings, in which:

[0025] Figure 1 A schematic diagram of a polycarbonate composite article according to one embodiment of the present invention is shown, wherein 10 represents a non-foamed polycarbonate film layer and 20 represents a foamed polycarbonate layer. DETAILED DESCRIPTION OF THE INVENTION

[0027] Some specific embodiments of the present invention will now be described with reference to the accompanying drawings for purposes of illustration and not limitation.

[0028] The descriptions of various features in this application can be combined with each other when there is no contradiction, and all fall within the protection scope required by this application.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. When the definition of a term in this specification conflicts with the meaning commonly understood by those of ordinary skill in the art to which the invention belongs, the definition described herein shall prevail.

[0030] According to a first aspect of the present invention, there is provided a polycarbonate composite article comprising:

[0031] an opaque expanded polycarbonate layer; and

[0032] a non-foamed polycarbonate film layer on the foamed polycarbonate layer;

[0033] in

[0034] The foamed polycarbonate layer comprises a polycarbonate resin, an impact modifier and optionally a flame retardant,

[0035] The non-foamed polycarbonate film layer comprises a polycarbonate resin and an optional UV stabilizer and has a thickness of 0.2-1.0 mm;

[0036] The ratio of the thickness of the non-foamed polycarbonate film layer to the thickness of the foamed polycarbonate layer is in the range of 1:3-1:20;

[0037] The polycarbonate composite article does not contain inorganic reinforcement materials.

[0038] Figure 1 A schematic diagram of a polycarbonate composite article according to one embodiment of the present invention is shown, wherein 10 represents a non-foamed polycarbonate film layer and 20 represents a foamed polycarbonate layer. It should be understood that Figure 1 It is intended to be illustrative, not limiting.

[0039] The foamed polycarbonate is opaque. According to the invention, the opaque characteristic is defined as that the corresponding material has a light transmittance of less than 5%, preferably less than 1%, most preferably less than 0.1% according to EN ISO 13468-2:2006, respectively measured at a layer thickness of 10 mm.

[0040] Preferably, the thickness of the foamed polycarbonate layer is in the range of 1.5-10.0 mm, preferably 2.0-6.0 mm, and more preferably 2.0-4.0 mm.

[0041] Preferably, the thickness of the non-foamed polycarbonate film layer is in the range of 0.2-0.6 mm (eg, 0.2-0.5 mm).

[0042] The ratio of the thickness of the non-foamed polycarbonate film layer to the thickness of the foamed polycarbonate layer is important in order to achieve good signal penetration performance.

[0043] Preferably, the ratio of the thickness of the non-foamed polycarbonate film layer to the thickness of the foamed polycarbonate layer is in the range of 1:3-1:15.

[0044] Those skilled in the art can select the type and amount of impact modifier, flame retardant and UV stabilizer as needed.

[0045] For example, the impact modifier can be one or more selected from the following: an impact modifier based on butadiene or styrene-butadiene rubber with a core-shell structure and methyl methacrylate-styrene grafted (MBS), a silicone-acrylate rubber with a core-shell structure, a core-shell impact modifier based on acrylate rubber, and the like.

[0046] Preferably, the core-shell impact modifier based on butadiene or styrene-butadiene rubber is an impact modifier based on butadiene or styrene-butadiene rubber grafted with methyl methacrylate or methyl methacrylate-styrene copolymers, such as Kane Ace M732 available from Kaneka, and Paraloid available from Dow Chemicals. TM EXL2650J, EXL2690 and EXL2691J, etc.

[0047] Suitable silicone-acrylate rubbers having a core-shell structure can be prepared from alkyl methacrylates and / or alkyl acrylates, a crosslinking agent and a grafting agent. In this context, exemplary and preferred alkyl methacrylates and / or alkyl acrylates are C 1 To C 8 Alkyl esters, for example, methyl ester, ethyl ester, n-butyl ester, tert-butyl ester, n-propyl ester, n-hexyl ester, n-octyl ester, n-lauryl ester and 2-ethylhexyl ester; halogenated alkyl esters, preferably halogenated C 1 To C 8 Alkyl esters, such as chloroethyl acrylate, and mixtures of these monomers. Particularly preferred is n-butyl acrylate.

[0048] Monomers having more than one polymerizable double bond can be used as crosslinkers for the polyalkyl (meth)acrylate rubber component of the silicone-acrylate rubber. Examples of preferred crosslinking monomers are esters of unsaturated monocarboxylic acids having 3 to 8 carbon atoms with unsaturated monohydric alcohols having 3 to 12 carbon atoms or saturated polyhydric alcohols having 2 to 4 OH groups and 2 to 20 carbon atoms, for example, ethylene glycol dimethacrylate, propylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate and 1,4-butylene glycol dimethacrylate. Such crosslinkers can be used alone or as a mixture of at least two crosslinkers.

[0049] Exemplary and preferred grafting agents are allyl methacrylate, triallyl cyanurate, triallyl isocyanurate or mixtures thereof. Allyl methacrylate can also be used as a crosslinking agent. Such grafting agents can be used alone or as a mixture of at least two grafting agents.

[0050] The crosslinking agent and the grafting agent are present in an amount of 0.1 wt % to 20 wt %, based on the total weight of the polyalkyl (meth)acrylate-rubber component of the silicone-acrylate rubber.

[0051] Preferred silicone-acrylate rubbers suitable for use are, for example, Metablen S-2100, S-2001, S-2006, etc. available from Mitsubishi Rayon, and Kane Ace MR-01 from Kaneka Corporation.

[0052] Preferred acrylate rubber based core-shell impact modifiers are methyl methacrylate grafted acrylate rubber based impact modifiers, including Paraloid available from Dow Chemicals. TM EXL2311, EXL2313, EXL2315, EXL2300, EXL2330, and EXL2390; and Durastrength available from Arkema ® 410, 440 and 480.

[0053] Particularly preferred are silicone-acrylate based core-shell impact modifiers to improve low temperature impact resistance.

[0054] The above-mentioned impact modifiers may be used alone or in combination.

[0055] The amount of the impact modifier is preferably 1.0 wt % to 8.0 wt %, more preferably 1.0 wt % to 6.0 wt %, particularly preferably 2.0 wt % to 5.0 wt %, relative to the weight of the foamed polycarbonate layer.

[0056] The flame retardant may be a flame retardant commonly used in the field of polycarbonate materials, such as an organic phosphorus-based flame retardant, such as bisphenol A bis(diphenyl phosphate) (BDP), triphenyl phosphate (TPP), phosphazene, and resorcinol bis(diphenyl phosphate) (RDP).

[0057] The above flame retardants may be used alone or in combination.

[0058] If present, the flame retardant is preferably present in an amount ranging from 1.0 wt% to 5.0 wt%, and more preferably from 1.5 wt% to 3.0 wt%, relative to the weight of the foamed polycarbonate layer.

[0059] The UV stabilizer may be a UV stabilizer commonly used in the polycarbonate material field.

[0060] Suitable UV stabilizers are described, for example, in EP 1 308 084 A1, DE 102007011069 A1 and DE 10311063 A1.

[0061] Particularly suitable UV stabilizers are hydroxybenzotriazoles, for example 2-(3',5'-bis(1,1-dimethylphenyl)-2'-hydroxyphenyl)benzotriazole (Tinuvin® 234, BASF SE, Ludwigshafen), 2-(2'-hydroxy-5'-(tert-octyl)phenyl)benzotriazole (Tinuvin® 329, BASF SE, Ludwigshafen), 2-(2'-hydroxy-3'-(2-butyl)-5'-(tert-butyl)phenyl)benzotriazole (Tinuvin® 350, BASF SE, Ludwigshafen), bis(3-(2H-benzotriazolyl)-2-hydroxy-5-tert-octyl)methane (Tinuvin® 360, BASF SE, Ludwigshafen), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(hexyloxy)phenol (Tinuvin® 400, BASF SE, Ludwigshafen), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(hexyloxy)phenol (Tinuvin® 410, BASF SE, Ludwigshafen), 2-(2'-hydroxy-3'-(2-butyl)-5'-(tert-butyl)phenyl)benzotriazole (Tinuvin® 41 ...2'-hydroxy-3'-(2-butyl)- 1577, BASF SE, Ludwigshafen), and also benzophenone 2,4-dihydroxybenzophenone (Chimasorb® 22, BASF SE, Ludwigshafen) and 2-hydroxy-4-(octyloxy)benzophenone (Chimasorb® 81, BASF SE, Ludwigshafen), 2-acrylic acid, 2-cyano-3,3-biphenyl, 2,2-bis[[(2-cyano-1-oxo-3,3-diphenyl-2-propenyl)oxy]methyl]-1,3-propanediol ester (9CI) (Uvinul® 3030, BASF SE, Ludwigshafen), 2-2-hydroxy-4-(2-ethylhexyl)oxy]phenyl-4,6-di(4-phenyl)phenyl-1,3,5-triazine (Tinuvin® 1600, BASF SE, Ludwigshafen), SE, Ludwigshafen) or tetraethyl 2,2'-(1,4-phenylenedimethylene) dimalonate (Hostavin® B-Cap, Clariant AG). Mixtures of these UV stabilizers can also be used.

[0062] If present, UV stabilizers are preferably present in an amount ranging from 0.10 wt % to 1.00 wt % and more preferably from 0.10 wt % to 0.50 wt %, particularly preferably from 0.10 wt % to 0.30 wt %, relative to the weight of the non-foamed polycarbonate film layer.

[0063] Preferably, the foamed polycarbonate layer and the non-foamed polycarbonate film layer contain the same polycarbonate resin, so that the adhesion between the foamed polycarbonate layer and the non-foamed polycarbonate film layer is better.

[0064] In some embodiments, the polycarbonate composite article consists of the foamed polycarbonate layer and the non-foamed polycarbonate film layer.

[0065] In some embodiments, the density of the foamed polycarbonate layer is 0.80-1.18 g / cm 3 .

[0066] Lightweight and reduced signal loss may be achieved through the cells in the foamed polycarbonate layer.

[0067] A non-foamed polycarbonate film can be placed in a mold cavity and adhered to the inner surface of the mold, and then a polycarbonate composition comprising a polycarbonate resin, an impact modifier and an optional flame retardant can be injected into the cavity and foamed to form a foamed polycarbonate layer, thereby forming a polycarbonate composite article according to the present invention without using an additional adhesive.

[0068] Thus, in some embodiments, no adhesive is present between the non-foamed polycarbonate film layer and the foamed polycarbonate layer.

[0069] The non-foamed polycarbonate film layer in the polycarbonate composite product of the present invention can meet various appearance requirements, such as high gloss, different colors, and different decorative patterns can be realized on the film layer. In addition, the non-foamed polycarbonate film layer can provide waterproof, UV resistance, weather resistance, impact resistance, flame retardancy and other properties according to application requirements. It can be used outdoors or indoors to meet relevant performance requirements.

[0070] Compared with the existing non-foamed polycarbonate products with the same thickness, the polycarbonate composite product of the present invention can achieve improved signal penetration performance, better dimensional stability and light weight through the combination of the foamed polycarbonate layer and the non-foamed polycarbonate film layer.

[0071] The signal loss during the transmission of electromagnetic waves in the medium is affected by many factors. For the shell as a transmission medium, in addition to the thickness and the distance from the shell to the antenna, the dielectric constant Dk and loss factor Df of the material are two particularly critical factors. Dk is a macroscopic physical quantity that indicates the degree of polarization of the medium and the ability of the medium to store electrical energy, thereby characterizing the ability to hinder signal transmission. Df is a physical quantity that indicates the ability of the dielectric to cause signal loss. The higher the Dk, the higher the Df, which means that the ability of the medium to block signal transmission is stronger and the signal transmission loss is greater. For 5G signals, especially millimeter waves, it is necessary to reduce the Dk and Df of the antenna shell material to reduce signal loss. If the antenna shell has a two-layer or multi-layer structure, as mentioned above, S11 (return loss) and S21 (gain) are commonly used indicators to characterize the transmission performance of the antenna, and their units are dB.

[0072] Compared with the existing polycarbonate article having the same thickness, the polycarbonate composite article according to the present invention has relatively lower return loss (S11) and gain loss (S21).

[0073] According to a second aspect of the present invention, there is provided a method for preparing a polycarbonate composite article according to the present invention, comprising the following steps:

[0074] placing the non-foamed polycarbonate film on the inner surface of an injection mold and closing the mold to form a cavity; and

[0075] The foamed polycarbonate layer is formed by injecting and foaming a molten polycarbonate composition comprising a polycarbonate resin, an impact modifier, and optionally a flame retardant in the cavity.

[0076] By means of the above method, design freedom can be achieved. For example, different thicknesses of the non-foamed polycarbonate film can be selected, and a foamed polycarbonate layer with a desired thickness, cell size and density can also be formed by injection foaming.

[0077] The polycarbonate composition comprising a polycarbonate resin, an impact modifier and an optional flame retardant can be obtained by first mixing polycarbonate particles with the impact modifier and the optional flame retardant, followed by melting.

[0078] Based on the foaming mechanism, injection foaming processes can be physical foaming processes and chemical foaming processes. Physical foaming processes use physical methods to foam plastics. There are two main methods: the first method involves injecting a supercritical fluid (usually N 2 or CO 2 ) is mixed with a polymer melt under high pressure to form a single-phase solution; the single-phase solution is then injected into a cavity, and due to the pressure drop in the cavity, bubbles nucleate to form bubble seeds; as the mold cools, the bubble seeds continue to grow and produce an internal cellular structure; and subsequently, after solidification, a foamed part with a cellular size of about 5-100 microns is formed.

[0079] The second method involves adding hollow spheres to the plastic to form the foam, which creates the foaming effect.

[0080] Preferably, Trexel's MuCell ® Foaming technology is used to 2 As a supercritical fluid for physical foaming. Nitrogen is the most widely used physical foaming agent. 2 ) compared to nitrogen (N 2 ) is about 75% lower. 2 ) provides a more uniform cell structure and is a stronger foaming agent.

[0081] The chemical foaming process uses chemical reactions to generate gas to foam plastics. Foaming is achieved by introducing a chemical foaming agent into the plastic particles and decomposing the chemical foaming agent to release gas by heating the injection molding barrel and shearing heat of the screw. In addition, foaming can also be achieved by using the gas released by the chemical reaction between each component in the plastic composition.

[0082] Chemical blowing agents can be powders or shaped foam particles. Particle blowing agents can be, for example, XO-331 from Bergen or Hydrocerol from Clariant. ® During the injection molding process, these cells continue to grow until the mold cavity is completely filled and cooled to form the final cells.

[0083] The injection foaming process can reduce the internal stress and deformation of the obtained product. The bubbles grow evenly throughout the cavity and can reduce the shrinkage of the obtained product. Therefore, the deformation of the formed polycarbonate composite product is greatly reduced and the dimensional stability is good.

[0084] The desired weight reduction can be achieved by adjusting the injection process parameters.

[0085] The inventors have discovered that a composite article having an isotropic non-foamed polycarbonate film layer and a low density foamed polycarbonate layer can be used as an antenna housing having sufficient strength to allow a single antenna housing to be used over a wide range of electromagnetic bands.

[0086] Therefore, according to a third aspect of the present invention, there is provided a use of the polycarbonate composite article according to the present invention as an antenna housing.

[0087] When the polycarbonate composite article according to the present invention is used as an antenna housing, the non-foamed polycarbonate film layer is an outer layer exposed to the external environment, and the foamed polycarbonate layer is an inner layer close to the antenna.

[0088] The antenna housing according to the present invention can be used as a protective housing for large outdoor antennas, small indoor antennas, and antennas for portable electrical and electronic devices.

[0089] In particular, the antenna housing according to the present invention can be used as a 5G antenna housing.

[0090] The antenna housing according to the present invention can protect the 5G antenna from sunlight, rain, snow, hail and wind after being installed outdoors.

[0091] Polycarbonate composite articles can be designed to have a desired profile of appropriate size for use in many applications including antenna housings. When used as antenna housings, the antenna housings can have a profile of a cuboid, a cube, a semi-ellipsoid, a hemisphere, etc.

[0092] The non-foamed polycarbonate film layer provides UV resistance and / or impact resistance and prevents moisture from being absorbed into the foamed polycarbonate layer. The presence of moisture may degrade the mechanical and electrical properties of the antenna housing. The non-foamed polycarbonate layer provides structural strength corresponding to the strength and / or stiffness required at the desired mounting location of the antenna under the expected environmental conditions.

[0093] Compared with conventional polycarbonate antenna housings, the antenna housing according to the present invention can reduce the signal loss of electromagnetic waves in the 5G frequency band and provide a weight reduction of 5%-20%. Example

[0094] The concept, specific structure and technical effect of the present invention will be further described with reference to the embodiments so that those skilled in the art can fully understand the purpose, characteristics and effects of the present invention. Those skilled in the art can easily understand that the embodiments herein are only for illustrative purposes, and the scope of the present invention is not limited thereto.

[0095] equipment

[0096] Using an ENGEL 260-ton injection molding machine, which integrates the Mucell from Trexel ® Physical foaming system.

[0097] raw materials

[0098] The non-foamed polycarbonate films with thicknesses of 0.25 mm, 0.5 mm, 1 mm and 2 mm are from Covestro Polymers (China) Co., Ltd. under the name Makrofol ® DE1-4.

[0099] The injection molding raw material for the foamed polycarbonate layer was a polycarbonate composition from Covestro Polymers (China) Co., Ltd., which contained 3.5 wt% of Kane Ace MR-01 (an impact modifier from Kaneka Corporation) and 2.0 wt% of phosphazene, relative to the weight of the polycarbonate composition.

[0100] The supercritical fluid is nitrogen (N 2 ).

[0101] Measurement

[0102] Tensile modulus and yield stress were tested according to ISO 527-2:2012.

[0103] The dielectric constant Dk and loss factor Df were tested according to ASTM D150 using a 16451B dielectric test fixture from Keysight technologies, with the Keysight resonant cavity method used for the frequency range of 1.1 GHz-15.0 GHz and the Keysight waveguide transmission line method used for the frequency range of 18.0 GHz-50.0 GHz.

[0104] The simulation process is based on the CTS STUDIO SUITE 2014 (CST Microwave Studio) version authorized by Southeast University. In the simulation process, actual material properties are used, for example, copper is used for the metal feed structure. The measured Dk and Df of the non-foamed polycarbonate film and the foamed polycarbonate layer are used as the input data of the antenna housing, and the simulation output data are S11 and S21. S11 is one of the S parameters, which represents the return loss characteristics. This parameter represents the transmission efficiency of the antenna. The higher the value, the greater the energy reflected by the antenna itself, and the worse the transmission efficiency of the antenna. S21 is the forward transmission coefficient, that is, the gain, and the higher the value, the better the transmission efficiency of the antenna.

[0105] Comparative Example 1 (CE1)

[0106] The molten polycarbonate composition without supercritical fluid was injected into the mold cavity to obtain a non-foamed PC film product with a thickness of 4 mm and a density of 1.2 g / cm³. The injection molding process parameters are shown in Table 1.

[0107] Tables 2 and 3 show the appearance, mechanical properties, signal transmission performance and simulation results of the non-foamed PC product, respectively.

[0108] Comparative Example 2 (CE2)

[0109] The supercritical fluid (N 2 ) was injected into the mold cavity, and the injection process was adjusted so that a weight reduction of 7 wt% was achieved compared with the non-foamed polycarbonate product obtained in Comparative Example 1, and a foamed polycarbonate product with a thickness of 4 mm and a density of 1.12 g / cm³ was obtained. The injection foaming process parameters used are shown in Table 1.

[0110] Table 2 and Table 3 show the appearance, mechanical properties, signal transmission performance and simulation results of the product respectively.

[0111] Comparative Example 3 (CE3)

[0112] The supercritical fluid (N 2) was injected into the mold cavity, and the injection process was adjusted so that a weight reduction of 15 wt% was achieved compared with the non-foamed polycarbonate product obtained in Comparative Example 1, and a foamed polycarbonate product with a thickness of 4 mm and a density of 1.02 g / cm³ was obtained. The injection foaming process parameters used are shown in Table 1.

[0113] Table 2 and Table 3 show the appearance, mechanical properties, signal transmission performance and simulation results of the product respectively.

[0114] Comparative Example 4 (CE4)

[0115] A non-foamed polycarbonate film with a thickness of 2.00 mm was cut and placed on the inner surface of the mold. 2 ) was injected into the mold cavity, and the injection process was adjusted so that a weight reduction of 7.5 wt% was achieved compared with the non-foamed polycarbonate product obtained in Comparative Example 1, and a double-layer polycarbonate composite product with a thickness of 4 mm and an average density of 1.11 g / cm³ was obtained. The injection foaming process parameters are shown in Table 1.

[0116] Table 2 and Table 3 show the appearance, mechanical properties, signal transmission performance and simulation results of the product respectively.

[0117] Invention Example 1 (IE1)

[0118] A non-foamed polycarbonate film with a thickness of 0.25 mm was cut and placed on the inner surface of the mold. 2 ) was injected into the mold cavity. The injection foaming process was adjusted so that a weight reduction of 7 wt% was achieved compared to the non-foamed polycarbonate product obtained in Comparative Example 1, and a double-layer polycarbonate composite product with a thickness of 4 mm and an average density of 1.12 g / cm³ was obtained. The injection foaming process parameters are shown in Table 1.

[0119] Table 2 and Table 3 show the appearance, mechanical properties, signal transmission performance and simulation results of the product respectively.

[0120] Invention Example 2 (IE2)

[0121] A non-foamed polycarbonate film with a thickness of 0.50 mm was cut and placed on the inner surface of the mold. 2) was injected into the mold cavity, and the injection foaming process was adjusted to achieve a weight reduction of 7 wt% compared to the non-foamed polycarbonate product obtained in Comparative Example 1. A double-layer polycarbonate composite product with a thickness of 4 mm and an average density of 1.13 g / cm³ was obtained. The injection foaming process parameters are shown in Table 1.

[0122] Table 2 and Table 3 show the appearance, mechanical properties, signal transmission performance and simulation results of the product respectively.

[0123] Inventive Example 3 (IE3)

[0124] A non-foamed polycarbonate film with a thickness of 0.25 mm was cut and placed on the inner surface of the mold. 2 ) was injected into the mold cavity, and the injection foaming process was adjusted to achieve a weight reduction of 15 wt% compared to the non-foamed polycarbonate product obtained in Comparative Example 1. A double-layer polycarbonate composite product with a thickness of 4 mm and an average density of 1.03 g / cm³ was obtained. The injection foaming process parameters are shown in Table 1.

[0125] Table 2 and Table 3 show the appearance, mechanical properties, signal transmission performance and simulation results of the product respectively.

[0126] Invention Example 4 (IE4)

[0127] A non-foamed polycarbonate film with a thickness of 0.50 mm was cut and placed on the inner surface of the mold. 2 ) was injected into the mold cavity, and the injection foaming process was adjusted so that a weight reduction of 13 wt% was achieved compared with the non-foamed polycarbonate product obtained in Comparative Example 1, and a double-layer polycarbonate composite product with a thickness of 4 mm and an average density of 1.04 g / cm³ was obtained. The injection molding process parameters are shown in Table 1.

[0128] Table 2 and Table 3 show the appearance, mechanical properties, signal transmission performance and simulation results of the product respectively.

[0129] Invention Example 5 (IE5)

[0130] A non-foamed polycarbonate film with a thickness of 1.00 mm was cut and placed on the inner surface of the mold. 2) was injected into the mold cavity, and the injection foaming process was adjusted to achieve a weight reduction of 11 wt% compared to the non-foamed polycarbonate product obtained in Comparative Example 1. A double-layer polycarbonate composite product with a thickness of 4 mm and an average density of 1.07 g / cm³ was obtained. The injection foaming process parameters are shown in Table 1.

[0131] Table 2 and Table 3 show the appearance, mechanical properties, signal transmission performance and simulation results of the product respectively.

[0132] Table 1: Process parameters for comparative examples (CE1-CE4) and inventive examples (IE1-IE5)

[0133]

[0134] MuCell Process Pressure (MPP)*: During the plasticizing phase, during gas injection, pressure is applied to the end of the screw in order to create and maintain a single-phase solution.

[0135] Table 2: Properties of products obtained in comparative examples (CE1-CE4) and inventive examples (IE1-IE5)

[0136]

[0137] As can be seen from Table 2, compared with the product prepared in Comparative Example 1 (CE1), the foamed polycarbonate products without PC film prepared by Comparative Example 2 (CE2) and Comparative Example 3 (CE3) can achieve a weight reduction of 7 wt% to 15 wt%, respectively, but there are obvious flow marks on the surface of the product and the mechanical properties are also significantly reduced.

[0138] As can be seen from Table 2, the double-layer polycarbonate composite products prepared in Inventive Example 1 (IE1) and Inventive Example (IE2) not only have improved mechanical properties at the same weight reduction as those in Comparative Example 2 (CE2), but also have good product surface quality without surface defects. Compared with the product prepared by Comparative Example 3 (CE3), the double-layer polycarbonate composite products prepared in Inventive Examples 3-5 (IE3-IE5) have improved mechanical properties. In addition, the surface of the polycarbonate composite products obtained in Inventive Examples 3-5 (IE3-IE5) is smooth and flawless, with a good appearance.

[0139] Table 3: Dk, Df, S11 and S21 of the products obtained in the comparative examples (CE1-CE4) and the inventive examples (IE1-IE5)

[0140]

[0141] As can be seen from Table 3, the double-layer polycarbonate composite products prepared in the inventive examples (IE 1-IE5) have different antenna echoes at different frequencies compared to the products prepared by the comparative example (CE 1). The return loss (S11) value of the double-layer polycarbonate composite products prepared in the inventive examples (IE1-IE 5) is relatively low, while the gain (S21) value is relatively high, indicating that the polycarbonate composite products of the present invention have improved signal penetration performance compared to the non-foamed polycarbonate products.

[0142] Compared with the product prepared in Comparative Example 4 (CE4) in which the thickness ratio of the non-foamed polycarbonate film layer to the foamed polycarbonate layer is 1:1, the double-layer polycarbonate composite products prepared in Inventive Examples (IE 1-IE 5) in which the thickness ratio of the non-foamed polycarbonate film layer to the foamed polycarbonate layer is 1:3 to 1:15 have relatively lower return loss (S11) and relatively higher gain (S21) for antennas at different frequencies, indicating that the polycarbonate composite product of the present invention has improved signal penetration performance.

Claims

1. A polycarbonate composite product for an antenna housing, comprising: an opaque expanded polycarbonate layer; and a non-foamed polycarbonate film layer on the foamed polycarbonate layer; in, The foamed polycarbonate layer comprises a polycarbonate resin, an impact modifier, and optionally a flame retardant; The non-foamed polycarbonate film layer comprises a polycarbonate resin and an optional UV stabilizer and has a thickness in the range of 0.2-1.0 mm, The ratio of the thickness of the non-foamed polycarbonate film layer to the thickness of the foamed polycarbonate layer is in the range of 1:3-1:20, The polycarbonate composite product does not contain inorganic reinforcing materials, The density of the foamed polycarbonate layer is 0.8-1.18 g / cm 3 .

2. The polycarbonate composite article according to claim 1, wherein the thickness of the foamed polycarbonate layer is in the range of 1.5-10 mm. 3 . The polycarbonate composite article according to claim 1 , wherein the thickness of the non-foamed polycarbonate film layer is 0.2-0.6 mm. 4 . The polycarbonate composite article according to claim 1 , wherein the content of the impact modifier in the foamed polycarbonate layer is 1 wt % to 8 wt % based on the weight of the foamed polycarbonate layer.

5. The polycarbonate composite article according to claim 1 or 2, wherein the polycarbonate resin used in the foamed polycarbonate layer is the same as that in the non-foamed polycarbonate film layer. 6 . The polycarbonate composite article according to claim 1 , wherein the polycarbonate composite article consists of the foamed polycarbonate layer and the non-foamed polycarbonate film layer.

7. The polycarbonate composite article of claim 4, wherein the impact modifier is a silicone-containing impact modifier.

8. The polycarbonate composite article according to claim 1 or 2, wherein the ratio of the thickness of the non-foamed polycarbonate film layer to the thickness of the foamed polycarbonate layer is in the range of 1:3-1:

15.

9. A method for preparing a polycarbonate composite article according to any one of claims 1 to 8, comprising the following steps: placing the non-foamed polycarbonate film on the inner surface of an injection mold and closing the mold to form a cavity; and The foamed polycarbonate layer is formed by injecting and foaming a molten polycarbonate composition comprising a polycarbonate resin, an impact modifier, and optionally a flame retardant in the cavity.

10. Use of the polycarbonate composite article according to any one of claims 1 to 8 as an antenna housing.

11. The use according to claim 10, wherein the non-foamed polycarbonate film layer is an outer layer exposed to the external environment, and the foamed polycarbonate layer is an inner layer close to the antenna.

Citation Information

Patent Citations

  • polycarbonate composition containing UV absorbers

    DE102007011069A1

  • UV stabilizer composition for transparent plastic packaging, e.g. for cosmetics or food, contains pentaerythritol tetrakis-2-cyano-3,3-diphenylacrylate and a hydroxybenzophenone derivative

    DE10311063A1

  • Synergistic UV absorber combination

    EP1308084A1

  • Low loss tri-band protective armor radome

    US20180241119A1

  • Radar transparent window for commercial buildings

    US4896164A